FREQUENCY OF GENE ACE I POLYMORPHISM I-D IN ATHLETES OF DIFFERENT SPORTS - Rocha,Agnelo Weber de Oliveira (2020)
ABSTRACT Introduction: The angiotensin-converting enzyme I-D (ACE) polymorphism gene is one of the most widely investigated genetic variations in sports science. Apparently, allele I is related to endurance sports, while allele D is related to power-strength activities. Nevertheless, studies have presented controversial results when it comes as to its occurrence in a variety of sports. Objective: This study aims to evaluate the frequency of gene ACE polymorphism I-D in professional athletes of collective or individual sports. Methods: Five mL blood were collected from 189 subjects divided into two groups: athletes (AG, n=127, wrestling, taekwondo, soccer, futsal and handball) and non-athletes (NAG, n=62). The athletes group was subdivided by group modalities, into: collective and individual. Both groups were further subdivided into male and female. Thus, we have the groups FAC= collective female, FAI= individual female, MAC= collective male, and MAI= individual male. The statistical analysis was carried out by frequency test, and the Hardy- Weinberg equilibrium by the x² test. Results: The results for the AG group indicated the following frequencies: DD=7%, ID=44% and II=49%. Allele frequency: D=29% and I=71%. For the NAG, the results were: DD=6.5%, ID=45.2% and II=48%. Allele frequency: D=29% and I=71%. The AG genotypic and allele frequencies did not differ statistically from those of the NAG (p= 0.982 and p= 0.984, respectively). However, we noticed that the genotypes II and ID frequencies were significantly higher than those of the DD. Conclusion: It can be concluded that the genotypic and allelic I-D frequencies of the ACE gene do not seem to influence performance in either group or individual sports. ACTN3 genotype frequencies did not vary significantly between male and female control subjects, and overall, there was no significant deviation from Hardy-Weinberg (H-W) equilibrium. Level of evidence I; Diagnostic studies–Investigating diagnostic test.